Perancangan Sistem Informasi Puskesmas Suka Merindu Berbasis Web - Maharani, Putri; Yusmiarti, Kusnita (Universitas Lembah Dempo, 2022)
Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts. As a service unit that directly deals with the community, puskesmas are required to have a system that allows health services to run effectively and optimally. With a management system that is still manual, there are often obstacles in finding patient data information, as well as difficulties in finding information on drug stocks and the process of making reports for the head of the puskesmas. For this reason, it is necessary to have a health center information system that can overcome these problems. This study aims to find a web-based information system design that can manage service activities at the Sukamerindu Public Health Center, Lahat Regency. The result of this research is a system design that can be used as a basis for making a web-based information system.